IMPLEMENTASI PERJANJIAN DALAM PENGELOLAAN LAHAN PARKIR ANTARA DESA ADAT DENPASAR DENGAN PEMERINTAH KOTA DENPASAR - I Wayan Arka (Kerta Dyatmika, 2021)
Abstract The Denpasar City Government through PERUMDA Bhukti Praja Sewakadarma has made several cooperation agreements with traditional villages in Denpasar City in terms of parking management. From the implementation side, the agreement between the Denpasar City government and the Denpasar traditional village is still experiencing various obstacles and is still not optimal, that the entrepreneur or land owner in this agreement does not get a profit sharing, if the land owner makes a lawsuit against both parties to get the right on the parking lot where they do business, what efforts will be made by both parties. Based on the background of the problems described above, the authors formulate the problem as follows: Does the Denpasar Traditional Village have the authority to manage parking areas in its Traditional Village area? And how is the authority of the Traditional Village to implement the agreement in the management of the parking lot between the Denpasar Traditional Village and the Denpasar City Government?The Denpasar Traditional Village has the authority to manage parking areas in its Traditional Village area where this authority is regulated in Article 103 of Law Number 6 of 2014 concerning Villages. The authority of the traditional village which consists of; regulate and implement government based on the original structure, management of areas under customary authority, preserving socio-cultural values ​​in traditional villages, resolving disputes that occur based on customary law in traditional villages that are in harmony with human rights principles by consensus, peace hearings with customary village court which is in accordance with the provisions of the applicable laws and regulations, maintains a sense of peace and order in the customary village community, develops customary law life in accordance with the socio-cultural conditions of the village community. So that the authority to manage parking areas in the area of ​​their Traditional Village is part of the authority of the Traditional Village in the field of managing areas that are under customary authority. The authority of the Traditional Village in implementing the agreement in the management of the parking area where the Denpasar Traditional Village and the Denpasar City Government are both legal entities so that they have the ability to enter into agreements, in this case the Traditional Village and the Denpasar City Government are in charge of the Perumda Bhukti Praja Sewakadharma to cooperate in management of parking lots in the Denpasar City area with a profit-sharing system, where both parties each have rights and obligations in accordance with the contents of the agreed agreement.